Tackling the social determinants of health: maximising community assets to help people receive the right support, in the right place, at the right time. - Maxwell, Douglas; Kelvin, Mark (International Journal of Integrated Care (IJIC))
Introduction: Tackling the social determinants of health requires a multi-level and multipartnered approach. Timely access to accurate information about services and support that can help people to live well is vital for good health and wellbeing. ALISS engages and empowers communities to find and share what matters to them. Short description of practice change implemented: A Local Information System for Scotland (ALISS) has its origins in the premise; "what is in my local community that can help me to live well?" ALISS is the system that facilitates the aggregation and dissemination of health and wellbeing information across Scotland. Along with being people powered (patients listing what they find helpful), ALISS shares information through an Application Programme Interface (API). This means that information added once is visible via a number of platforms. Organisations/people can 'claim' services so that they can maintain their own information in order to increase chance of accuracy. Aim and theory of change: Communities are often full of resources that can support people to live well but information about these resources is often invisible, inaccurate, or stored only in one place. If this information is findable, accurate, and relevant, people are more likely to receive the right support, in the right place, at the right time. Targeted population and stakeholders: In line with proportionate universalism, we prioritise populations that data suggests are most in need in then scale. Currently we are working with people that access foodbanks. 144,000 people accessed food through the Trussell Trust foodbanks in Scotland in 2016. There is a direct link between the people who use foodbanks and their level of health and financial inequality. Timeline: ALISS originated in 2009. Since then ALISS has started a redevelopment of the technical infrastructure and change in the service delivery. Our new platform will be launched in January 2018. Highlights: People powered information is now findable, accurate, and visible through several platforms. ALISS makes hidden social capital visible. ALISS is a unique example of coproduction. Comments on sustainability: ALISS is referenced in the NHS Scotland Chief Executive annual report for 2016 as a tool to support the aggregation and dissemination of health and wellbeing information across Scotland. Transferability: ALISS is open source. ALISS has been used to power the aggregation and dissemination of health and wellbeing information across England, with links being forged with Kaiser Permanente (USA). Conclusions: Strategic and statutory partners, such as Police Scotland and NHS 24 value trusted health and wellbeing information, including from third sector resources. Scaling and operational growth plan aligned to communities living with the highest levels of health and social inequality (<5% - 10% SIMD). Discussions: ALISS has always worked to the principle that individuals are always at the heart of development and planning. This coproduced approach is central to the success of the service. Lessons learned: Trying to coproduce a system that presents users with relevant and accurate search results from informal data has been the biggest challenge to ALISS.